An Overview of Honeybee Colony Losses in Buenos Aires Province, Argentina - Genchi García, María Laura (2019)
Honey bees (Apis mellifera) are essential for the ecosystem, so their loss threatens biodiversity and agriculture. Several factors have been proposed as possible causes of both massive losses and Colony Collapse Disorder. In August 2017 episodes of colony losses were registered in General Alvear, Buenos Aires province. The aim of the present study was to find possible causes of these events. The samples were screened for presence of several pathogens and the determination of maternal lineages was also performed. Seven out of ten colonies were positive for pathogens, but there was no high prevalence of any of them. It will be necessary to carry out a standardization of studies, and delineate boundaries that allow comparing cases in order to discriminate different types of mortality of colonies that occur worldwide.